Analisis Implementasi Manajemen Pendidikan Islam Melalui Fungsinya (Studi Kasus di SD Negeri Tangerang 14) - Azmiya Arsyla (INTIFA: Journal of Education and Language, 2025)
The success of Islamic education in state schools (public schools) in providing Islamic education is largely determined by management's ability to implement management professionally. This article aims to describe and analyze the implementation of Islamic education management at SDN Tangerang 14. To obtain data, the techniques used are observation, interviews and documentation. The data is generated using interactive techniques and continues continuously until completion so that the data is saturated as developed by Miles and Huberman (1994). The conclusion of this research is that in the Implementation of Islamic Education Management at SDN Tangerang 14 there are several functions of Education Management Implementation, including planning, organizing and supervising. Management implementation starts from planning with a mechanism for determining the direction and goals to be achieved by involving the Tangerang District Regional Coordinator, supervisors, school principals, teachers and committees. Furthermore, organization is carried out by distributing tasks and responsibilities to all school members through meetings before new teachings are implemented. Implementation of supervision is carried out by controlling the quantity and quality of personnel work through class supervision, meetings, and budget use audits carried out through meetings with the school committee.   ABSTRAK Keberhasilan suatu pendidikan Islam dalam sekolah negeri (sekolah umum) dalam menyelenggarakan pendidikan Islam sangat ditentukan oleh kemampuan manajemen dalam mengimplemenasikan manajemen secara professional. Artikel ini mempunyai tujuan untuk mendeskripsikan dan menganalisis implementasi manajemen pendidikan islam di SDN Tangerang 14. Untuk mendapatkan data, teknik yang digunakan yaitu observasi, wawancara dan dokumentasi. Data yang dihasilkan dengan teknik interaktif dan berlangsung terus menerus sampai tuntas sehingga datanya jenuh seperti yang dikembangkan oleh Miles dan Huberman (1994). Kesimpulan penelitian ini, bahwa dalam Implementasi Manajemen Pendidikan Islam di SDN Tangerang 14 terdapat beberapa fungsi Implementasi Manajemen Pendidikan antara lain, perencanaan, pengorganisasian, dan pengawasan. Implementasi Manajemen dimulai dari perencanaan dengan mekanisme menentukan arah dan tujuan yang akan dicapai dengan melibatkan korwil Kecamatan Tangerang, pengawas, kepala sekolah, guru, dan komite. Selanjutnya, pengorganisasian dilakukan dengan pembagian tugas dan tanggung jawab kepada seluruh warga sekolah melalui rapat sebelum ajaran baru dilaksanakan. Implementasi pengawasan dilakukan dengan mengontrol kuantitas dan kualitas kerja personil melalui supervisi kelas, rapat, serta audit penggunaan anggaran yang dilakukan melalui rapat bersama komite sekolah.